Influence of a Roundup formulation on glyphosate effects on steroidogenesis and proliferation of bovine granulosa cells in vitro. (December 2017) - Perego, Maria Chiara; Caloni, Francesca; Cortinovis, Cristina; Schutz, Luis F.; Albonico, Marco; Tsuzukibashi, Denise; Spicer, Leon J.
Abstract: Glyphosate ( N -phosphonomethyl-glycine) is a non-selective systemic herbicide widely used worldwide. The purpose of this study is to determine if glyphosate alone (GLPH) or in formulation with Roundup (G-RU) can affect granulosa cell proliferation and steroid production. Four experiments were conducted. In Exp. 1, 10 and 300 μg/mL of GLPH had no effect (P > 0.05) on cell numbers, estradiol or progesterone production, whereas 10 and 300 μg/mL of G-RU dramatically decreased (P < 0.05) cell numbers and estradiol and progesterone production. In Exp. 2, G-RU at 0.1 μg/mL had no significant effect whereas G-RU at 10 μg/mL decreased (P < 0.05) GC numbers, progesterone and estradiol production. In the absence of IGF1 but presence of FSH, 1 μg/mL of G-RU decreased (P < 0.05) estradiol production, whereas in the presence of IGF1 and FSH, 1 μg/mL of G-RU increased (P < 0.05) cell numbers, progesterone and estradiol production. In Exp. 3, IGF1 significantly increased cell numbers (by 2.8-fold) and estradiol (by 17.8-fold) and progesterone (by 6.1-fold) production. GLPH at 10 μg/mL alone had no significant effect on FSH-induced (i.e., basal) or FSH plus IGF1-induced cell numbers, estradiol or progesterone production. However, G-RU at 10 μg/mL significantly inhibited FSH plus IGF1-induced cell numbers, estradiol and progesterone production by 65%–91%. In Exp. 4, 48 h treatment of G-RU had no significant effect on viability of attached cells. In conclusion, the present studies demonstrate that GLPH and particularly G-RU may have the potential to impair reproductive function in cattle. Highlights: Glyphosate in formulation impaired bovine granulosa cell proliferation. Glyphosate in formulation impaired steroid production. Glyphosate in formulation had more potent effects than glyphosate alone. Glyphosate in formulation may act as an endocrine disruptor chemical in cattle.